Flexural behaviour of a cold-formed steel-concrete composite beam with channel type shear connector - an experimental and analytical study - Palanivelu, Sangeetha (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Steel-concrete composite structures are widely used in the current construction of bridges and multi-storey buildings. The effect of shear connectors in a cold-formed steel-composite beam was studied under flexure. The number of channel connectors in the specimen was varied and the same was compared with a specimen without shear connectors. The performance and failure of cold-formed steel-composite beams were then studied.
Keywords: composite beam; beam; cold-formed steel; channel connectors; load; belka stalowo-betonowa; kompozyt; złącze kanałowe; obciążenia